CAMPO GRANDE NEWS OVER TWO DECADES: CONTINUITIES, RUPTURES, AND THE FUTURE OF DIGITAL JOURNALISM (Editora Impacto Científico, 2025)
This article revisits—two decades later—the analysis of Campo Grande News to identify continuities, ruptures, and trends in local digital journalism (2005–2025). Drawing on non-participant observation in the newsroom and interviews with management, editors, and reporters, it compares routines, technologies, and the relationship with the audience. Findings indicate the current centrality of WhatsApp in newsgathering, editing, and distribution—with gains in agility and record-keeping (audio/messages), but losses in spontaneity and greater control by sources. In terms of product, the digital outlet evolved toward responsive layout, visual standardization, and image processing (optimization and lightweight formats), supported by an in-house CMS and SEO practices. Editorially, soft news (e.g., the Lado B section) has expanded without abandoning daily coverage of matters of public interest, guided by an Editorial Style Manual that seeks to standardize criteria, curation, and ethics in the face of high staff turnover.DOI: https://doi.org/10.56238/edimpacto2025.090-026